2002
DOI: 10.1016/s0002-9440(10)64366-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Promotes Smooth Muscle Cell Proliferation and Dedifferentiation in Atherosclerotic Lesions of Human Apo(a) Transgenic Rabbits

Abstract: Elevated plasma lipoprotein(a) [Lp(a)]levels constitute an independent risk factor for the development of atherosclerosis. However, the mechanism underlying Lp(a) atherogenicity is unclear. Recently, we demonstrated that Lp(a) may potentially be proatherogenic in transgenic rabbits expressing human apolipoprotein(a) [apo(a)]. In this study, we further investigated atherosclerotic lesions of transgenic rabbits by morphometry and immunohistochemistry. On a cholesterol diet, human apo(a) transgenic rabbits had mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 42 publications
(31 reference statements)
1
46
0
1
Order By: Relevance
“…In addition to oxLDL, Lp (a), another atherogenic lipoprotein, may also lead to an inflammatory process by inducing the expression of adhesion molecules on endothelial cells, the chemotaxis of monocytes, and the proliferation of smooth muscle cells (38). In one of our recent studies using transgenic rabbits expressing human apo (a), we demonstrated that Lp (a) in transgenic rabbits which do not have endogenous apo (a) showed increased aortic atherosclerosis in comparison with control rabbits.…”
Section: Lipoproteins and Inflammationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to oxLDL, Lp (a), another atherogenic lipoprotein, may also lead to an inflammatory process by inducing the expression of adhesion molecules on endothelial cells, the chemotaxis of monocytes, and the proliferation of smooth muscle cells (38). In one of our recent studies using transgenic rabbits expressing human apo (a), we demonstrated that Lp (a) in transgenic rabbits which do not have endogenous apo (a) showed increased aortic atherosclerosis in comparison with control rabbits.…”
Section: Lipoproteins and Inflammationmentioning
confidence: 99%
“…Atherosclerotic lesions in transgenic rabbits are characterized by increased cellular proliferation, and Lp (a) is often deposited in the lesions. We initially hypothesized that Lp (a) may stimulate smooth muscle cell dedifferentiation in addition to proliferation and found that a large number of intimal cells are positively stained with SMemb, a monoclonal antibody against the smooth muscle myosin heavy chain isoform (38). In addition, Lp (a) has the ability to inhibit fibrinolytic activity by increasing plasma plasminogen activator-1 production (38).…”
Section: Lipoproteins and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…The intimal lesions were measured using a computerized image analysis system and expressed as microscopic lesion areas. 28 To study cellular components, lipoprotein and LPL deposits in the lesions, we performed immunohistochemical staining using the following monoclonal antibodies against macrophages (RAM-11), smooth muscle a-actin (HHF35), oxidized LDL (FOH1a/ DLH3), 29 and LPL (5D2). 30 …”
Section: Quantification Of Aortic Atherosclerosismentioning
confidence: 99%